A deterministic simulation study of embryo marker-assisted selection for age at first calving in Nellore (Bos indicus) beef cattle - Rosa, Artur J.M.; Bijma, Piter; Oliveira, Henrique Nunes de [UNESP]; Lôbo, Raysildo B.; van Arendonk, Johan A.M. (Sociedade Brasileira de Genética, 2007)
We used deterministic simulation of four alternative multiple ovulation and embryo manipulation (MOET) closed nucleus schemes to investigate the benefits of using marker-assisted selection (MAS) of Nellore (Bos indicus) beef cattle embryos prior to transplantation to reduce the age at first calving (AFC). We found that MAS resulted in increased genetic gain as compared to selection without AFC quantitative trait loci (AFC-QTL) information. With single-stage selection the genetic response (GR) increased as follows: GR = 0.68% when the AFC-QTL explained 0.02 of the AFC additive genetic variance (sigma2A); GR = 1.76% for AFC-QTL explaining 0.05 sigma2A; GR = 3.7% for AFC-QTL explaining 0.1 sigma2A; and GR = 55.76% for AFC-QTL explaining 0.95 sigma2A. At the same total selected proportion, two-stage selection resulted in less genetic gain than single stage MAS at two-years of age. A single stage selection responses of > 95% occurred with pre-selected proportions of 0.4 (0.1 sigma2A explained by AFC-QTL), 0.2 (0.3 sigma2A explained by AFC-QTL) and 0.1 (0.5 sigma2A explained by AFC-QTL), indicating that the combined use of MAS and pre-selection can substantially reduce the cost of keeping recipient heifers in MOET breeding schemes. When the number of recipients was kept constant, the benefit of increasing embryo production was greater for the QTL explaining a higher proportion of the additive genetic variance. However this advantage had a diminishing return especially for QTL explaining a small proportion of the additive genetic variance. Thus, marker assisted selection of embryos can be used to achieve increased genetic gain or a similar genetic response at reduced expense by decreasing the number of recipient cows and number of offspring raised to two-years of age.
Keywords: age at first calving; Beef cattle; Marker assisted selection; pre-selection; quantitative trait loci